(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The task of undevstanding the contemporary religions situation from the perspective of social and philosophical cognition is posed. The latter involves the study of universal laws and society features, considered in integrity with the interrelation of its sides – individual, culture and society. The worldview foundations of Kazakhstani society is taken into consideration. On the basis of the problem’s and historical analysis do the conclusion that the religion, in-fi rst, is an integral part of sociocultural life today. Secondly, being the universal phenomenon of universal culture, it has, at the same time, lines of an originality. And, thirdly, the most optimal answer to calls of spiritual and religious life is the organic combination of the culturological and sociocultural, all-civilization and regional approaches promoting identifi cation, preservation and consolidation of cultural and historical sense of religion in the conditions of globalization. Key words: religion, mythical-religious picture of the world of Turk’s ethnos, religious situation, modern Kazakhstan society.